Analisis Hubungan Ketepatan Penulisan Diagnosis dengan Keakuratan Kode Diagnosis pada Kasus Obstetri dan Ginekologi di Rumah Sakit Tk. IV DKT Kediri - Hartaty Sarma Sangkot; Prima Soultoni Akbar; Endang Sri Dewi; Avid Wijaya; Citra Alifa Puspaningtyas (Jurnal Rekam Medik & Manajemen Informasi Kesehatan, 2022)
Activity of determining the disease code and writing the diagnosis must be in accordance with the correct medical terminology and the classification rules that apply in Indonesia, namely ICD-10 in order to get the right and accurate code. This study aims to analyze the relationship between the accuracy of writing a diagnosis and the accuracy of the diagnosis code in obstetrics and gynecology cases at Rumah Sakit Tk. IV DKT Kediri. The method used in this research is analytic research with cross sectional approach. Based on Slovin's formula, the sample used was 100 medical record documents of inpatients. The sampling technique used is simple random sampling. The data collection technique used observation with a checklist instrument. Data on the accuracy of writing the diagnosis and the accuracy of the diagnosis code were analyzed univariately, while the relationship between the accuracy of writing the diagnosis and the accuracy of the diagnosis code was analyzed using SPSS with Chi-Square test. The results showed that the accuracy of writing the diagnosis was 56%, the accuracy of the diagnosis code was 43%, and there was a relationship between the accuracy of writing the diagnosis and the accuracy of the diagnostic code for obstetrics and gynecology cases at Rumah Sakit Tk. IV DKT Kediri (p < 0.025).